(untitled) (Libellarium: journal for research in the field of information and related sciences, 2017)
In the last two decades higher education in Europe has been going through deep changes, based on the vision of united educational space and educational reform as a consequence of many social and technological changes. Although many discussions have been held, many conferences organised, and serious research papers published on the topic of changes, internationalization and Europeanisation of education of information experts, there are still debates on conceptual issues and an urge for a new, innovative approach to structure and organisation of higher education institutions, including information sciences field. The aim of this paper is to point out to new trends in European higher education that have taken place in information sciences as well. These trends have stimulated search for solutions that would, starting from traditional competences and critically approaching new possibilities, enable the offer of attractive and sustainable study programmes that would be flexible enough to react on labour market needs for experts in the digital environment and new educational profiles.